Bioprocess Optimization for the Production of Arthrospira (Spirulina) platensis Biomass Enriched in the Enzyme Alkaline Phosphatase - Giorgos Markou (Bioengineering, 2021)
The enzyme alkaline phosphatase (ALP) is gaining interest because it exerts bioactive properties and may be a potentially important therapeutic agent for many disorders and diseases. Microalgae are considered an important novel source for the production of diverse bio-compounds and are gaining momentum as functional foods/feeds supplements. So far, studies for the production of ALP are limited to mammalian and partly to some heterotrophic microbial sources after its extraction and/or purification. Methods: Arthrospira was cultivated under P-limitation bioprocess and the effect of the P-limitation degree on the ALP enrichment was studied. The aim of this work was to optimize the cultivation of the edible and generally-recognized-as-safe (GRAS) cyanobacterium Arthrospira platensis for the production of single-cell (SC) biomass enriched in ALP as a potential novel functional diet supplement. Results: The results revealed that the relationship between intracellular-P and single-cell alkaline phosphatase (SC-ALP) activity was inverse; SC-ALP activity was the highest (around 50 U g−1) when intracellular-P was the lowest possible (around 1.7 mg-P g−1) and decreased gradually as P availability increased reaching around 0.5 U g−1 in the control cultures. Under the strongest P-limited conditions, a more than 100-fold increase in SC-ALP activity was obtained; however, protein content of A. platensis decreased significantly (around 22–23% from 58%). Under a moderate P-limitation degree (at intracellular-P of 3.6 mg-P g−1), there was a relatively high SC-ALP activity (>28 U g−1) while simultaneously, a relative high protein content (46%) was attained, which reflects the possibility to produce A. platensis enriched in ALP retaining though its nutritional value as a protein rich biomass source. The paper presents also results on how several parameters of the ALP activity assay, such as pH, temperature etc., and post-harvest treatment (hydrothermal treatment and biomass drying), influence the SC-ALP activity.